PSXIV-7 Transcriptomic analysis of varying immune responses in BVDV challenged cattle. (7th December 2018) - Fleming, D; Gill, C
Abstract: Bovine viral diarrhea virus (BVDV) is a widespread disease of cattle caused by a pestivirus. Infection can be both sub-clinical and persistent in herds and can predispose infected and non-infected cattle to bovine respiratory disease (BRD), a serious co-infection. In spite of the effort to understand and increase the immune response to BVDV, there are gaps in the knowledge of the efficacy for other cattle disease vaccines, such as BRD, and whether there are differences between the protection afforded by modified live (ML) or killed (K) vaccines, and if they offer cross-protection to BVDV. The objective of the project is to determine evidence of cross-protection and differential gene expression in response to a sub-clinical BVDV challenge after ML and K BRD vaccinations. The project examined gene expression of white blood cells from three treatment groups (no vaccine, K, ML) of Nellore-Angus crossbred cattle intranasally infected with BVDV after vaccination for BRD. The ML group received vaccination 35 days prior to infection and the K group received a primary and booster vaccination at 56 and 35 days pre-infection. Samples (n = 5 per treatment) for clinical and gene expression analysis were collected and processed from challenge day 14. Transcriptomic analysis of RNA-Seq data was performed using DESeq2 within the Galaxy.org web portal. Vaccination with the BRD-ML led to lower BVDa, BVD2, and BVDb viral titers (p < 0.001) when compared to the BRD-K vaccine. Gene expression analysis showed the largest number of statistically significant genes were related to the ML vs. the control animals and encompassed downregulation of genes that inhibit T-cell proliferation. The observed results show better efficacy in cross-protection from the ML vaccine possibly linked to farther reaching effects on genes linked to adaptive immunity.